Modeling the kinetics of peroxidase inactivation, colour and texture changes of Portuguese cabbage (Brassica oleracea L. var. costata DC) during UV-C light and heat blanching - Cruz, R. M. S. (2016)
The e ects of heat blanching and UV-C light followed by heat on Portuguese cabbage peroxidase (POD), colour and texture were studied in the temperature range of 80-95 °C. POD inactivation, lightness (L) and yellowness (b) colour changes were described by a rst-order reaction model. The greenness (a) colour and texture ( rmness) changes followed a two fraction kinetic model behaviour. The temperature e ect was well described by the Arrhenius law. At lower temperatures the combined treatment showed higher POD inactivation. Colour and texture parameters did not show signi cant di erences between treatments. Long processing times turned the leaves slightly darker, decreased greenness, yellowness and rmness. Short processing times increased the rmness and greenness of the leaves. The treatment at 80 °C for 90 seconds reduced 90% of POD, retaining 98% of lightness and 92% of yellowness and improved the green colour (130%) and rmness (125%). At 80 °C the heat blanching required 7.4 min to inactivate 90% of the enzyme activity, reducing lightness, greenness, yellowness and rmness to 92%, 68%, 62% and 61%, respectively. The present ndings will help to optimize the Portuguese cabbage blanching conditions.